2016
DOI: 10.1177/1355819615612826
|View full text |Cite
|
Sign up to set email alerts
|

How is feedback from national clinical audits used? Views from English National Health Service trust audit leads

Abstract: National cancer audit and feedback is used to improve services, but their impact could be enhanced by improving the data quality and relevance of feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 17 publications
0
36
0
2
Order By: Relevance
“…Evidence from a systematic review 176 and a study 177 examining private feedback suggest that it can motivate providers to respond through raising awareness of performance in relation to peers and through peer competition. Evidence from studies comparing private and public reporting 35,39,118,179 suggests that while clinicians are intrinsically motivated to maintain good patient care, the public reporting of performance places additional pressure on them to take steps to improve patient care, particularly for poor performers.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence from a systematic review 176 and a study 177 examining private feedback suggest that it can motivate providers to respond through raising awareness of performance in relation to peers and through peer competition. Evidence from studies comparing private and public reporting 35,39,118,179 suggests that while clinicians are intrinsically motivated to maintain good patient care, the public reporting of performance places additional pressure on them to take steps to improve patient care, particularly for poor performers.…”
Section: Theorymentioning
confidence: 99%
“…The authors note that such comparative data 'motivated trusts to improve, driven on by a competitive spirit'. 177 The authors observed that those interviewees who had been able to make changes had done so in the light of looking at how they compared with trusts locally, while those who did not make changes did not have these data available to them. These findings support theories of benchmarking, that peer comparison motivates providers to improve through peer competition.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As the PREM is personalized and narrative, aggregating qualitative data is more time-consuming and difficult compared to quantitative PREMs. Providing feedback from the macro level is found to clarify reporting needs and potentially increasing managements' engagement in writing the quality report [25].…”
Section: Discussionmentioning
confidence: 99%